If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -6) + 9 = 13x + -7 + -2 Reorder the terms: 3(-6 + 5x) + 9 = 13x + -7 + -2 (-6 * 3 + 5x * 3) + 9 = 13x + -7 + -2 (-18 + 15x) + 9 = 13x + -7 + -2 Reorder the terms: -18 + 9 + 15x = 13x + -7 + -2 Combine like terms: -18 + 9 = -9 -9 + 15x = 13x + -7 + -2 Reorder the terms: -9 + 15x = -7 + -2 + 13x Combine like terms: -7 + -2 = -9 -9 + 15x = -9 + 13x Add '9' to each side of the equation. -9 + 9 + 15x = -9 + 9 + 13x Combine like terms: -9 + 9 = 0 0 + 15x = -9 + 9 + 13x 15x = -9 + 9 + 13x Combine like terms: -9 + 9 = 0 15x = 0 + 13x 15x = 13x Solving 15x = 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 15x + -13x = 13x + -13x Combine like terms: 15x + -13x = 2x 2x = 13x + -13x Combine like terms: 13x + -13x = 0 2x = 0 Divide each side by '2'. x = 0 Simplifying x = 0
| 0x-4y=-20 | | 48x^5y^7+12x^4y^6+16x^4y=0 | | (x-10)(x)=0 | | 1+3(6b-3)=-134 | | (3/5)x=6 | | 13=-1/2y | | y=0.5+1 | | 5/(x+4)-6x/(3x+12)+7/(2x+8) | | 1/2m=35 | | .6x=1.5 | | 15x-9=13x-9 | | 8x-4(-7.5)=2 | | 6x-4y= | | 2p+3p-p=9-15-6 | | 180=(x+5)(x+1)x | | 6(0.15+w)=10 | | Z-4.6=-2.2-3z | | 8q-42=-26 | | -54=6z-18 | | 3/2(2x-2)1/5= | | 2(3t-6)=10t-t-6 | | 0.3+2.6=4.4 | | (275)(373-x)(.444)=(100)(x-295)(4.184) | | 3y+10=82 | | -1/7y^7*5/8y^2 | | 5m+25=-65 | | 2x=6-y | | 3.7x-4=2.7x | | (6x-3)(-2x-14)= | | (-6x+3)(2x-14)= | | (-3x+9)(4x-2)= | | 6*9-9y=-54 |